p38-Mitogen Activated Kinases Mediate a Developmental Regulatory Response to Amino Acid Depletion and Associated Oxidative Stress in Mouse Blastocyst Embryos - Bora, Pablo; Thamodaran, Vasanth; Šušor, Andrej; Bruce, Alexander W. (Frontiers in Cell and Developmental Biology, 2019)
Maternal starvation coincident with preimplantation development has profound consequences for placental-foetal development, with various identified pathologies persisting/manifest in adulthood; the ‘Developmental Origin of Health and Disease’ (DOHaD) hypothesis/model. Despite evidence describing DOHaD-related incidence, supporting mechanistic and molecular data relating to preimplantation embryos themselves are comparatively meagre. We recently identified the classically recognised stress-related p38-mitogen activated kinases (p38-MAPK) as regulating formation of the extraembryonic primitive endoderm (PrE) lineage within mouse blastocyst inner cell mass (ICM). Thus, we wanted to assay if PrE differentiation is sensitive to amino acid availability, in a manner regulated by p38-MAPK. Although blastocysts appropriately mature, without developmental/morphological or cell fate defects, irrespective of amino acid supplementation status, we found the extent of p38-MAPK inhibition induced phenotypes was more severe in the absence of amino acid supplementation. Specifically, both PrE and epiblast (EPI) ICM progenitor populations remained unspecified and there were fewer cells and smaller blastocyst cavities. Such phenotypes could be ameliorated, to resemble those observed in groups supplemented with amino acids, by addition of the anti-oxidant NAC (N-acetyl-cysteine), although PrE differentiation deficits remained. Therefore, p38-MAPK performs a hitherto unrecognised homeostatic early developmental regulatory role (in addition to direct specification of PrE), by buffering blastocyst cell number and ICM cell lineage specification (relating to EPI) in response to amino acid availability, partly by counteracting induced oxidative stress; with clear implications for the DOHaD model.